NQPC-15 DEVELOPMENT OF BRAIN TUMOR SURVIVORSHIP PROGRAM. (3rd December 2022) - Saito, Norihiko; Hirai, Nozomi; Kushida, Naoki; Sato, Sho; Hiramoto, Yu; Fujita, Satoshi; Nakayama, Haruo; Hayashi, Morito; Ito, Keisuke; Sakurai, Takatoshi; Iwabuchi, Satoshi
Abstract: Introduction: Brain tumor patients suffer from psychological distress and various sequelae from the moment they are diagnosed with a brain tumor, during and after treatment. Although the number of brain tumor survivors is increasing as a result of improved treatment outcomes for brain tumors, the support system is not sufficient. We, in collaboration with the University of California San Francisco Brain Tumor Center, have established a multidisciplinary professional staff of physicians, nurses, pharmacists, rehabilitation therapists, nutritionists, and social workers to support brain tumor patients, their families, and care givers. The brain tumor survivorship program is designed to support brain tumor patients, their families, and caregivers. This report describes their efforts. Methods: This program started in December 2021. We asked relevant departments in the hospital to cooperate with the program. In July 2022, the "Brain Tumor Survivorship Care Program 360" website was opened to the public. Results: As of the end of August 2022, there were 9 participants, of which 7 were patients and 2 were care givers. Of these, two were patients being treated at other hospitals. Various information is provided on the website. Web meetings are also held to provide a place where participants can communicate directly with each other. When participants were asked about their requests for the program, many of them requested information on treatment, public services, and a place for communication among patients. Discussion: Brain tumor patients face not only life-threatening but also painful symptoms associated with the impairment of their own physical motor and cognitive functions, which they had possessed until then. Through the survivorship program, we will continue to scientifically examine and develop a support system for the various survival-related issues that brain tumor patients and their families experience from diagnosis to the end of life.